Shrimp Cracker Making Business in Indragiri Hilir - Bathara, Lamun; Nugroho, Firman; Nasution, Tio Afandi; Simanjuntak, Asnika Putri; Nasution, Musyirna Rahmah (Jurnal Perikanan dan Kelautan, 2025)
Indragiri Hilir is one of the districts with extensive waters and abundant fishery production. The potential for capture fisheries in Indragiri Hilir Regency is very large. In 2021, the potential for capture fisheries was 53,057.13 tons. Shrimp is a fishery commodity with high economic value and a favorite of Indonesian exports in the fisheries sector. Shrimp crackers are a series of food processing processes that combine tapioca flour with fresh shrimp to produce crispy snacks with a distinctive flavor. This process involves several critical stages that must be carried out carefully to produce high-quality products. Shrimp crackers are one of Indonesia's traditional snacks that have a distinctive taste and are in demand by various groups. Based on this, this study aims to determine how the shrimp cracker-making business process in Indragiri Hilir will be carried out in 2024. The research results obtained from this study are the shrimp cracker-making business in Indragiri Hilir, precisely in Tanah Merah Village, starting from the preparation, processing, and packaging stages. Shrimp crackers have been marketed to regions including Irian Jaya, Batam, Pekanbaru, Palembang, and Java. The development of the shrimp cracker processing business not only increases the livelihood of local people but also contributes to reducing unemployment in the area.